Retropubic tissue fixation system tensioned mini‐sling carried out under local anesthesia cures stress urinary incontinence and intrinsic sphincter deficiency: 1‐year data. (14th May 2017) - Nakamura, Ryoko; Yao, Masahiro; Maeda, Yoshiko; Fujisaki, Akiko; Sekiguchi, Yuki
Abstract : Objectives: To assess the outcomes of the tissue fixation system midurethral sling for the treatment of intrinsic sphincter deficiency. Methods: We retrospectively studied a total of 96 intrinsic sphincter deficiency patients treated with the tissue fixation system midurethral sling at Yokohama Motomachi Women's Clinic from 2006 to 2015. We evaluated intraoperative and 1‐year postoperative results. Regarding the cure rate, we divided patients into three groups: (i) patients with maximum urethral closure pressure <20 and Valsalva leak point pressure <65 combined ( n = 17); (ii) patients with maximum urethral closure pressure <20 ( n = 55); and (iii) patients with Valsalva leak point pressure <65 ( n = 47). Results: The median age was 63 years (range 38–89 years). The median operating time including local anesthesia was 24 min (range 12–55 min) and median blood loss was 5.0 mL (range 3–69 mL). All operations were day surgery under local anesthesia. Postoperative pain was minimal. All patients were discharged the same day. There were no intraoperative complications except one bladder perforation. There were no tape rejections. The 1‐year postoperative cure rates were: 88.2% among patients with maximum urethral closure pressure <20 and Valsalva leak point pressure <65, 90.9% for patients with maximum urethral closure pressure <20, and 85.1% among patients with Valsalva leak point pressure <65. Conclusions: The tissue fixation system midurethral sling operation is a simple, safe and effective operation for older women with intrinsic sphincter deficiency, and it can be carried out under local anesthesia.